Gut barrier breach and glucose dysregulation: the dual threat of food-transformed microplastics - Zhe Chen; Yihua Yuan; Chuxin Zhang; Xu Li; Fei Ren; Dingchang Xue; Juan Shao; Keming Yun; Zhongyuan Guo (Food Research International, 2026)

Hydrodynamics acts as a key driver of microplastics transport throughout surface and surface-subsurface water interaction zones: A mechanistic review and research priorities - Xiaohua Huang; Yuchuan Meng; Yu Chen; Peng Zhao; Li Liu; Keming Tang (Journal of Hazardous Materials, 2026)

Mechanistic insights into CO2-enhanced in-situ pyrolysis of tar-rich coal: Experiments and ReaxFF molecular dynamics simulations - Wei Guo; Panxi Yang; Zunyi Yu; Hongqiang Li; Keming Fu; Xuanzhi Hao; Yuxing Zheng; Zihao Tao; Jing Wang; Bolun Yang; Zhiqiang Wu (Fuel, 2026)

Antagonistic effects of temperature and salinity on total dimethylsulfoniopropionate (DMSPt) production in a river-dominated bay during extreme winter events - Lingxiao Li; Jing Sun; Zhengguo Cui; Tao Jiang; Zhenhao Liu; Keming Qu; Hongsheng Wang; Qingjing Hu; Hongwu Cui; Shenghui Zhang (Estuarine, Coastal and Shelf Science, 2026)

Predictive design of entrained-flow coal pyrolysis with cross-scale framework for high-value and low-carbon operation - Panxi Yang; Zunyi Yu; Keming Fu; Yuxing Zheng; Wei Guo; Zibo Huang; Hongqiang Li; Bolun Yang; Wenjing Zhou; Zhiqiang Wu (Chemical Engineering Journal, 2026)

IP3R1 regulates AMPK-mTOR-mediated mitochondrial function to influence the oocyte-to-embryo transition of porcine - Ran Teng; Ning Xu; Xingfu Chen; Yuening Xing; Xiaoqing Sun; Dexin Yuan; Keming Huang; Lepeng Gao; Suo Li (Theriogenology, 2026)

Study on the daytime heat gain and nighttime heat dissipation characteristics of microchannel PV/T modules - Keming Xu; Rongji Xu; Hongbing Chen; Gaochao Li; Ziyu Xing (Energy and Buildings, 2026)

Comparative Transcriptome and Gene-Editing Analyses Reveal the Molecular Mechanism of Albinism in the Taiwanese Loach - Rongyun Li; Xiaohui Bai; Xiaojuan Cao; Shuang Hao; Keming Liu; Zhang Luo; Jian Gao; Yaoxin Wang; Yunbang Zhang; Lin Ma; Jufeng Jiang (Marine Biotechnology, 2026)

From protein-like to humic-like substances: Feed-derived regulation of dissolved organic matter transformation in RAS - Ying Bai; Ruijie Ma; Zhengguo Cui; Hao Li; Hongwu Cui; Yong Xu; Jianlei Chen; Keming Qu (Aquacultural Engineering, 2026)

EEG-RCPNet: a cross-subject cognitive impairment detection model based on limited-channel eeg signals - Zining Wang; Minghui Zhao; Keming Cao; Lulu Zhao; Shuo Zhang; Yamei Bai; Jianqing Li; Chengyu Liu (Medical & Biological Engineering & Computing, 2026)

Unveiling the mechanism: DOM from chemically pretreated corncobs drives denitrification via mediating microbial community succession - Ying Bai; Ruijie Ma; Zhengguo Cui; Hongwu Cui; Weiman Gong; Wei Dong; Hao Li; Yong Xu; Jianlei Chen; Keming Qu (Journal of Environmental Chemical Engineering, 2026)

Adaptation Mechanisms of Aquatic Animals to Saline–Alkaline Water Aquaculture: Physiological, Energetic and Molecular Perspectives - Yingsha Qu; Huichen Li; Bo Zhang; Hongwu Cui; Jianlei Chen; Yong Xu; Zhengguo Cui; Keming Qu; Hao Li (Fishes, 2026)
Saline–alkaline water constitutes a vital strategic non-traditional fishery resource in China, characterized by high pH values, elevated carbonate alkalinity, and complex ionic compositions. These extreme environmental conditions impose significant stress on aquatic animals, mainly by inducing ionic toxicity and disrupting acid–base regulatory mechanisms. Such disruptions subsequently lead to osmotic imbalance, metabolic dysregulation, and immunosuppression, thus restricting the survival and growth of aquatic species in aquaculture systems. Consequently, the sustainable development of the saline–alkaline aquaculture is imperative for enhancing production efficiency and promoting the utilization of marginal land and water resources. This review comprehensively summarizes the current status of saline–alkaline aquaculture and highlights the stress-inducing impacts of salinity, alkalinity, and specific ionic ratios on teleost fishes and crustaceans. It further explores key adaptive mechanisms, including osmoregulatory and ionoregulatory strategies, bioenergetic trade-offs related to oxygen consumption and ammonia excretion, coordinated antioxidant and innate immune responses, as well as recent findings from multi-omics research. This review aims to offer a scientific foundation for the selection and breeding of saline–alkaline-tolerant strains, the precise regulation of aquaculture water environments, and the development of ecological aquaculture models in saline–alkaline regions, thereby facilitating the sustainable utilization of saline–alkaline land and water resources.

Efficient elimination of highly lethal Vibrio parahaemolyticus in shrimp aquaculture by a vibriophage - Mingrui Li; Huaijin Jiang; Keming Shi; Haoyu Huang; Xiaojun Wang; Fang Li; Ke Pan; Yunlan Yang; Rui Zhang (Fish & Shellfish Immunology, 2026)

Numerical study on three-dimensional coupling characteristics for electromagnetism and flow in flat linear induction pump - Heyao Li; Zhuqian Zhang; Lixin Yang; Keming Bi; Xin Yan; Haojie Zhang; Xiao Chen (Annals of Nuclear Energy, 2026)

Distinct ecophysiological characteristics of two genetically similar vibriophages - Wenqing Li; Runqi Zhu; Keming Shi; Huiyu Ding; Shiying Ren; Song Xu; Jing Zhao; Nianzhi Jiao; Yunlan Yang; Rui Zhang (Marine Life Science & Technology, 2026)

A broad-spectrum vibriophage with potential for phage therapy against Vibrio alginolyticus in shrimp aquaculture - Keming Shi; Huiyu Ding; Wanxuan Zhong; Wenqing Li; Min Hsiao; Bu Xu; Haipeng Guo; Jing Zhao; Jie Xu; Demin Zhang; Yunlan Yang; Rui Zhang (Aquaculture, 2026)

Significant effects of temperature and pH on zooplankton dynamics: Implications for ocean warming and acidification - Minghao Li; Dongsheng Ding; Chuanxia Liu; Zhengguo Cui; Wei Dong; Jun Sun; Keming Qu; Yuqiu Wei (Ocean & Coastal Management, 2026)

Hematotoxicity of Fe- and Cr-based metal–organic framework nanoparticles in rockfish Sebastes schlegelii - Yiling Li; Junyu Ye; Meiyu Wang; Yang Gao; Bin Xia; Zhengguo Cui; Keming Qu (Marine Environmental Research, 2026)

Novel composite essential oil nanoemulsion stabilized via a dual strategy of covalent chemical bonding and compositional synergy: Application to hairtail (Trichiurus lepturus) preservation - Meng Wang; Keming Zhang; Yanjun Wen; Yujin Li; Changhu Xue; Zihao Wei (Food Chemistry, 2026)

A subsidence prediction model-driven InSAR phase unwrapping approach for large-gradient deformation in mining areas - Kegui Jiang; Keming Yang; Zijun Yang; Qiyong Zhang; Wenwen Li; Xinxin Zhang (Advances in Space Research, 2026)

Effects of PD-1 inhibitors on ovarian function-based on two-sample mendelian randomization and visualization experimental validation - Jiaxin Zheng; Na Zhu; Chang Liu; Xiang Li; Keming Zhang; Zhuo Yang; Danbo Wang; Bo Liu (Reproductive Toxicology, 2025)

Cloning, Expression, and Odorant Binding Characteristics of the Chemosensory Protein 1 in Asecodes hispinarum, a Parasitoid of the Coconut Leaf Beetle - Keming Li; Fuping Lu; Huazhou Wu; Dezhao Lou; Peipan Gong; Tao Geng; Tao Jin; Jin Zhang; Shuchang Wang (Journal of Chemical Ecology, 2025)

Crop rotation mitigates soil fungal diversity loss under warming or increased moisture - Zhibo Zhou; Keming Yang; David Tissue; Zhong Wei; Le Li; Zhe Tang; Lukuan Fu; Hanqin Li; Tingting Sheng; Hongwei Liu; Yingjun Zhang; Fengge Zhang (Agriculture, Ecosystems & Environment, 2025)

Rayleigh wave dispersion and attenuation characterized by couple-stress-based poroelasticity - Guoqiang Li; Pei Zheng; Keming Zhang (Wave Motion, 2025)

Waterborne and dietary accumulation and toxicity of iron-based metal-organic framework in cladoceran Moina mongolica Daday - Yiling Li; Zihan Liu; Zhengguo Cui; Keming Qu; Bin Xia (Journal of Hazardous Materials, 2025)

Synergistic effect of Cu-Ni bimetallic doping in Cd0.8Zn0.2S for enhanced photocatalytic CO2 reduction: Modulating the d-band center for improved activity - Haonan Li; Keming Li; Shuhan Sun; Yongjia Zhang; Zhanfeng Li; Yanting Tian (Journal of Environmental Chemical Engineering, 2025)

Longitudinal analysis of metabolic liver disease induced by high-starch diets in largemouth bass (Micropterus salmoides) - Xixuan Huang; Xuemei Ouyang; Li Wang; Kun Xue; Haodong Yu; Chenlei Liao; Feifei Chen; Keming Rong; Xuezhen Zhang (Aquaculture International, 2025)

Carnitine content and its influencing factors in marine animals collected from China’s offshore region and the Northwest Pacific Ocean - Yufeng Gao; Zhengguo Cui; Jianwei Li; Keming Qu; Qingkui Wang; Lanlan He; Xiangtao Liu; Xiner Zhao; Liuyizhi Zhang; Lingxiao Li; Ying Bai; Fangqun Dai; et al. (Acta Oceanologica Sinica, 2025)

Impact of Water Velocity on Litopenaeus vannamei Behavior Using ByteTrack-Based Multi-Object Tracking - Jiahao Zhang; Lei Wang; Zhengguo Cui; Hao Li; Jianlei Chen; Yong Xu; Haixiang Zhao; Zhenming Huang; Keming Qu; Hongwu Cui (Fishes, 2025)
In factory-controlled recirculating aquaculture systems, precise regulation of water velocity is crucial for optimizing shrimp feeding behavior and improving aquaculture efficiency. However, quantitative analysis of the impact of water velocity on shrimp behavior remains challenging. This study developed an innovative multi-objective behavioral analysis framework integrating detection, tracking, and behavioral interpretation. Specifically, the YOLOv8 model was employed for precise shrimp detection, ByteTrack with a dual-threshold matching strategy ensured continuous individual trajectory tracking in complex water environments, and Kalman filtering corrected coordinate offsets caused by water refraction. Under typical recirculating aquaculture system conditions, three water circulation rates (2.0, 5.0, and 10.0 cycles/day) were established to simulate varying flow velocities. High-frequency imaging (30 fps) was used to simultaneously record and analyze the movement trajectories of Litopenaeus vannamei during feeding and non-feeding periods, from which two-dimensional behavioral parameters—velocity and turning angle—were extracted. Key experimental results indicated that water circulation rates significantly affected shrimp movement velocity but had no significant effect on turning angle. Importantly, under only the moderate circulation rate (5.0 cycles/day), the average movement velocity during feeding was significantly lower than during non-feeding periods (p

Unraveling Spiroplasma eriocheiris: Morphological motility, virulence mechanisms, and host defense strategies in crustacean pathogenesis - Siyuan Zhang; Jiaxin Chen; Yalan Jiang; Yan Li; Chenbin Zhu; Yujun Tang; Yaqi Wang; Hong Huang; Keming Zhong; Yingrui Xiong; Jiaofeng Peng; Peng Liu (Aquaculture, 2025)

A clean utilization process for low-grade ball Clay: Preparation of PAFS and applications in LC3 - Longxin Zhao; Yi'an Li; Yuxuan Wang; Zihan Chen; Keming Chen; Ruifeng Guo; Cundi Wei; Wenqing Li; Fagui Qiu; Shiding Miao (Journal of Cleaner Production, 2025)

Functionalization-dependent toxicity of MIL-101 metal-organic frameworks to phytoplankton Chlamydomonas reinhardtii - Meiyu Wang; Bin Xia; Zhengguo Cui; Keming Qu; Yiling Li (Aquatic Toxicology, 2025)

Lipid droplet-targeting fluorescent probes for monitoring hydrogen sulfide in ferroptosis - Chen Wang; Zhaomin Wang; Bingyan Li; Ziye Yang; Ruo Yang; Keming Zhu; Yong Liu (Analytica Chimica Acta, 2025)

The Application of Digital Twin Technology in the Development of Intelligent Aquaculture: Status and Opportunities - Jianlei Chen; Yong Xu; Hao Li; Xinguo Zhao; Yang Su; Chunhao Qi; Keming Qu; Zhengguo Cui (Fishes, 2025)
Aquaculture is vital for global food security but faces challenges like disease, water quality control, and resource optimization. Digital twin technology, a real-time virtual replica of physical aquaculture systems, emerges as a transformative solution. By integrating sensors and data analytics, it enables monitoring and optimization of water quality, feed efficiency, fish health, and operations. This review explores the current adoption status of digital twins in aquaculture, highlighting applications in real-time monitoring and system optimization. It addresses key implementation challenges, including data integration and scalability, and identifies emerging opportunities for advancing sustainable, intelligent aquaculture practices.

Network pharmacology, molecular docking, molecular dynamics simulation, and experiment verification analysis to reveal the action mechanism of RenShen Guipi Wan in the treatment of anemia - Tingli Qu; Nan Zhang; Chen Li; Xuyuan Liu; Keming Yun; Quan An (Biotechnology Letters, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

Multisource remote sensing and ensemble learning for multidimensional monitoring of heavy metals on mine surfaces - Yanru Li; Keming Yang; Xinru Gu; Lishun Peng; Xinyang Chen (Environmental Geochemistry and Health, 2025)

Self-healing waterborne polyurethane originated from waste PET and their composites with polypyrrole for stretchable strain sensor - Keming Zhu; Lan Yang; Xing Zhou; Xuan Zhang; Yaya Hao; Fan Li; Wanqing Lei; Qi Wang; Guosheng Wang (Chemical Engineering Journal, 2025)

Implications of seawater characteristics on dissolved heavy metals in near-shore surface waters of the Yellow Sea - Minghao Li; Dongsheng Ding; Yong Xu; Qian Yang; Jun Sun; Keming Qu; Zhengguo Cui; Yuqiu Wei (Marine Pollution Bulletin, 2025)

Ecological risk assessment for BDE-47 in marine environment based on species sensitivity distribution method - Ying Bai; Ruijie Ma; Zhengguo Cui; Liping Liu; Dongsheng Ding; Qingjing Hu; Bin Xia; Zhaochuan Li; Haibo Zhang; Keming Qu (Marine Environmental Research, 2025)

Integrating larval zebrafish model and network pharmacology for screening and identification of edible herbs with therapeutic potential for MAFLD: A promising drug Smilax glabra Roxb. - Yinjuan Xiong; Xixuan Huang; Yuxin Li; Yukang Nie; Haodong Yu; Yaqi Shi; Jiajie Xue; Zhehui Ji; Keming Rong; Xuezhen Zhang (Food Chemistry, 2025)

Multi-omics analysis and longitudinal study of reprogramming by dietary creatine to endogenous metabolism in largemouth bass (Micropterus salmoides) - Haodong Yu; Yukang Nie; Xinping Ran; Shaoyun Li; Keming Rong; Xuezhen Zhang (Fish Physiology and Biochemistry, 2025)

Early warning system for nocardiosis in largemouth bass (Micropterus salmoides) based on multimodal information fusion - Zhenming Huang; Haixiang Zhao; Zhengguo Cui; Lei Wang; Hao Li; Keming Qu; Hongwu Cui (Computers and Electronics in Agriculture, 2024)

Polydopamine-assisted minute fabrication of vertically aligned ZIF-L membranes for CO2/N2 separations - Keming Zhang; Sihui Li; Xiaohe Tian; Rui Zhang; Xiaoting Feng; Qingnan Wang; Yanting Tang; Chenlu Liu; Hongxia Gao; Shaofei Wang (Chemical Engineering Journal, 2024)

Spatial-temporal pattern of ecosystem services and sustainable development in representative mountainous cities: A case study of Chengdu-Chongqing Urban Agglomeration - Liang Chen; Ying Yao; Keming Xiang; Xiaoai Dai; Wenyu Li; Hang Dai; Ke Lu; Weile Li; Heng Lu; Yang Zhang; Huan Huang; Meilian Wang (Journal of Environmental Management, 2024)

Effect of hydraulic retention time on denitrification performance and microbial communities of solid-phase denitrifying reactors using polycaprolactone/corncob composite - Hongwu Cui; Yuna Feng; Weibin Lu; Lu Wang; Hao Li; Yu Teng; Ying Bai; Keming Qu; Yingying Song; Zhengguo Cui (Marine Pollution Bulletin, 2024)

A comparative analysis of growth and nutritional quality of the hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) in a simulated pond system and a recirculating aquaculture system - Yingsha Qu; Zhendong Yin; Xiangyu Fan; Haiyan Hu; Hongwu Cui; Zhengguo Cui; Keming Qu; Hao Li (Frontiers in Marine Science, 2024)
Groupers, as a popular economic fish species, are now more frequently cultured in land-based facilities, however, traditional pond-farming methods are plagued by frequent disease outbreaks, unstable economic benefits, and environmental pollution. To explore a new farming mode for a grouper, an 80-day cultivation experiment was conducted using both a simulated pond system (SPS) and a recirculating aquaculture system (RAS). The research aims to evaluate the growth performance, health (pathogenic bacteria, intestinal microbiota), off-flavor compounds (geosmin, 2-methylisoborneol), and nutritional component (amino acids, fatty acid composition and content) of a hybrid grouper ( Pinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂ ) under different aquaculture systems. The results showed that the hybrid grouper in a RAS exhibited better growth performance; the concentration of Vibrio in the fish tissue in the RAS was significantly lower than that in the SPS. Moreover, the content of fresh amino acids in the RAS was significantly higher, and the levels of saturated fatty acids (SFAs) and ω-6 polyunsaturated fatty acids (ω-6PUFAs) were significantly higher in the RAS. This finding indicates the superior flavor and nutritional value of the grouper. These results prove that the RAS is suitable for the widespread cultivation of grouper.

Environmental risk mitigation of lambda-cyhalothrin using tryptophan-modified magnetic nanoparticles: A sustainable emergency response strategy - An Zhao; Linzhi Cai; Ran Li; Zhihao Zheng; Keming Jiao; Yunhao Gao (Chemical Engineering Journal, 2024)

A comprehensive review of research on indoor cognitive performance using electroencephalogram technology - Nan Zhang; Chao Liu; Jiaxin Li; Keming Hou; Jing Shi; Weijun Gao (Building and Environment, 2024)

Vision-based dual network using spatial-temporal geometric features for effective resolution of fish behavior recognition with fish overlap - Haixiang Zhao; Yuankai Wu; Keming Qu; Zhengguo Cui; Jianxin Zhu; Hao Li; Hongwu Cui (Aquacultural Engineering, 2024)

A fish appetite assessment method based on improved ByteTrack and spatiotemporal graph convolutional network - Haixiang Zhao; Hongwu Cui; Keming Qu; Jianxin Zhu; Hao Li; Zhengguo Cui; Yuankai Wu (Biosystems Engineering, 2024)

Dietary creatine promotes creatine reserves, protein deposition, and myofiber hyperplasia in muscle of juvenile largemouth bass (Micropterus salmoides) - Haodong Yu; Ya He; Mu Qin; Li Wang; Keming Rong; Xuezhen Zhang (Aquaculture, 2024)

ZIF-8 Gel/PIM-1 mixed matrix membranes for enhanced H2/CH4 separations - Keming Zhang; Xianye Luo; Sihui Li; Xiaohe Tian; Qingnan Wang; Chenlu Liu; Yanting Tang; Xiaoting Feng; Rui Zhang; Shuangfeng Yin; Shaofei Wang (Chemical Engineering Journal, 2024)

Physiological and transcriptomic analysis reveals the toxic and protective mechanisms of marine microalga Chlorella pyrenoidosa in response to TiO2 nanoparticles and UV-B radiation - Lin Zhu; Sulan Feng; Yu Li; Xuemei Sun; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

Interplays between plants and environmental factors determine pullout resistance on different revegetated slopes in mining areas - Zhang Chen; Oumeng Qiao; Yong Liu; Keming Ma; Huiping Song; Chengjun Li (Journal of Environmental Management, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

The characteristics of trimethylamine N-oxide content in different classes of marine animals over the coastal and offshore areas of China - Ning An; Hongsheng Wang; Jianwei Li; Lanlan He; Yufeng Gao; Lingxiao Li; Qingkui Wang; Zhengguo Cui; Keming Qu; Qingjing Hu (Marine Pollution Bulletin, 2023)

Dual CNN cross-teaching semi-supervised segmentation network with multi-kernels and global contrastive loss in ACDC - Keming Li; Guangyuan Zhang; Kefeng Li; Jindi Li; Jiaqi Wang; Yumin Yang (Medical & Biological Engineering & Computing, 2023)

Identifying the key factors affecting the trimethylamine N-oxide content of teleost fishes collected from the marginal seas of China and the epipelagic zone of the northwest Pacific Ocean - Qingjing Hu; Wanyu Zhao; Keming Qu; Ning An; Lingxiao Li; Yuqiu Wei; Ying Bai; Tao Jiang; Jufa Chen; Fangqun Dai; Hongsheng Wang; Zhengguo Cui (Science of The Total Environment, 2023)

Role and anti-inflammatory mechanisms of acupuncture and moxibustion therapy on pain relief through NOX-ROS-NLRP3 pathway in CCI rats models - Wang Jinying; Li Keming; Tang Hanqing; Zhang Xuqing; Fatima Muccee; Luo Xuan; Liu Yalin; Song Meiye; Zhang Shumin; Chandrabose Selvaraj; Sher Zaman Safi (Molecular Biology Reports, 2023)

Research on the spatiotemporal prediction of mining deformation with subcritical extraction integrated with D-InSAR technology - Keming Yang; Zhixian Hou; Xiangping Wei; Wei Gao; Yanru Li; Xinming Ding; Shuang Wang; Yaxing Li; Hengqian Zhao (Advances in Space Research, 2023)

Spatial distribution and potential ecological risk assessment of heavy metals in the sediments of fishing ports along the coasts of the Yellow Sea and Bohai Sea - Hongsheng Wang; Qingjing Hu; Dongsheng Ding; Lingxiao Li; Ning An; Keming Qu; Chuanxia Liu; Mingying Zhou; Zhengguo Cui (Marine Pollution Bulletin, 2023)

High dimethylsulfoniopropionate concentrations in the surface seawater over the marginal seas of China and the Northwest Pacific Ocean during May–July of 2021 following La Niña - Lingxiao Li; Zhengguo Cui; Keming Qu; Hongsheng Wang; Ruohan Song; Xiaoke Hu; Shenghui Zhang; Tao Jiang; Mingying Zhou; Qingjing Hu (Marine Pollution Bulletin, 2023)

RIN enhances plant disease resistance via root exudate-mediated assembly of disease-suppressive rhizosphere microbiota - Keming Yang; Ruixin Fu; Haichao Feng; Gaofei Jiang; Omri Finkel; Tianyu Sun; Mingchun Liu; Baowen Huang; Shan Li; Xiaofang Wang; Tianjie Yang; Yikui Wang; et al. (Molecular Plant, 2023)

Dietary selenium requirement for on-growing grass carp, Ctenopharyngodon idellus - Feifei Chen; Ziyi Zhang; Li Wang; Haodong Yu; Xuezhen Zhang; Keming Rong (Aquaculture, 2023)

Hazardous substances and their removal in recirculating aquaculture systems: A review - Hao Li; Zhengguo Cui; Hongwu Cui; Ying Bai; Zhendong Yin; Keming Qu (Aquaculture, 2023)

Scale transfer learning of hyperspectral prediction model of heavy metal content in maize: From laboratory to satellite - Yanru Li; Keming Yang; Hengqian Zhao (International Journal of Remote Sensing, 2023)

A reference vector based multiobjective evolutionary algorithm with Q-learning for operator adaptation - Keming Jiao; Jie Chen; Bin Xin; Li Li (Swarm and Evolutionary Computation, 2023)

Evolution of Meteorological Conditions during a Heavy Air Pollution Event under the Influence of Shallow Foehn in Urumqi, China - Xia Li; Keming Zhao; Shiyuan Zhong; Xiaojing Yu; Zhimin Feng; Yuting Zhong; Ayitken Maulen; Shuting Li (Advances in Atmospheric Sciences, 2023)

Hydrocarbons removal and microbial community succession in petroleum-contaminated soil under hydrogen peroxide treatment - Bing Yang; Mi Zhou; Yuan Meng; Keming Chen; Jie Xu; Xiangfu Huang; Yucheng Liu; Lingli Li; Lili Ma; Mingyan Chen (Environmental Science and Pollution Research, 2022)

Non-destructive study on identifying and monitoring of Cu-Pb pollution in corn based on near-infrared spectroscopy - Yanru Li; Keming Yang; Bing Wu; Jianhong Zhang; Qianqian Han; Wei Gao (Environmental Science and Pollution Research, 2022)

The toxicity of perfluorodecanoic acid is mainly manifested as a deflected immune function - Keming Li; Qian Zhao; Ziyan Fan; Shouyin Jia; Qing Liu; Fengyan Liu; Shili Liu (Molecular Biology Reports, 2022)

Tsp-1 is involved in DNA stability through Tgf-β1 activation domain in cone photoreceptor 661 W cells - Pei Chen; Chang Liu; Jing Zhang; Xi Chen; Xuan Liu; Shengyu He; Anqi He; Shuilian Chen; Jin Qiu; Yan Li; Zihua Jiang; Keming Yu; et al. (Cell and Tissue Research, 2022)

The Change in the Neutrophil/Lymphocyte Ratio Predicts the Prognosis of Patients with Cryptococcal Meningitis - Keming Zhang; Hang Li; Lei Zhang; Wanqing Liao; Liangqi Cai; Xinhua Li; Weihua Pan; Qilong Zhang (Mycopathologia, 2021)

Molecular Analysis Associated with Early Flowering Mutant in Brassica napus - Jiawang Mao; Yanhua Yang; Ningning Wang; Keming Zhu; Yulong Li; Zheng Wang; Xiaoli Tan (Journal of Plant Biology, 2021)

Integrative transcriptomic and metabolomic analyses provide insight into the long-term submergence response mechanisms of young Salix variegata stems - Qingwei Zhang; Shaohu Tang; Jianqiu Li; Chunfen Fan; Libo Xing; Keming Luo (Planta, 2021)

Magnesium alleviates aluminum toxicity by promoting polar auxin transport and distribution and root alkalization in the root apex in populus - Zhen Zhang; Dunyi Liu; Hongjun Meng; Shengting Li; Shufeng Wang; Zhongchun Xiao; Juanjuan Sun; Longran Chang; Keming Luo; Nannan Li (Plant and Soil, 2020)

The Monitoring of the Pollution Degree of Maize Under Copper Stress - Chao Zhang; Keming Yang; Kunpeng Rong; Feng Cheng; Yan Li (Journal of the Indian Society of Remote Sensing, 2020)

Spectral Characteristics and the Study of Pollution Degree of Maize Leaves Under Copper and Lead Stress - Chao Zhang; Keming Yang; Yan Li; Feng Cheng; Kunpeng Rong (Journal of the Indian Society of Remote Sensing, 2020)

Sex difference in the association of body mass index and BDNF levels in Chinese patients with chronic schizophrenia - Fang Yang; Keming Wang; Xiangdong Du; Huiqiong Deng; Hanjing Emily Wu; Guangzhong Yin; Yuping Ning; Xingbing Huang; Antonio L. Teixeira; João de Quevedo; Jair C. Soares; Xiaosi Li; et al. (Psychopharmacology, 2019)

PtrMYB57 contributes to the negative regulation of anthocyanin and proanthocyanidin biosynthesis in poplar - Shuzhen Wan; Chaofeng Li; Xiaodong Ma; Keming Luo (Plant Cell Reports, 2017)

Contrasting elevational diversity patterns for soil bacteria between two ecosystems divided by the treeline - Guixiang Li; Guorui Xu; Congcong Shen; Yong Tang; Yuxin Zhang; Keming Ma (Science China Life Sciences, 2016)

Acute Blockage of Notch Signaling by DAPT Induces Neuroprotection and Neurogenesis in the Neonatal Rat Brain After Stroke - Zhongxia Li; Jiangping Wang; Congying Zhao; Keming Ren; Zhezhi Xia; Huimin Yu; Kewen Jiang (Translational Stroke Research, 2016)

Identification and characterization of a wood-associated NAC domain transcription factor PtoVNS11 from Populus tomentosa Carr. - Li Yang; Yisu Hou; Xin Zhao; Wanxiang Lu; Yongli Li; Fan Yang; Shaohu Tang; Keming Luo (Trees, 2015)

A poplar R2R3-MYB transcription factor, PtrMYB152, is involved in regulation of lignin biosynthesis during secondary cell wall formation - Chaofeng Li; Xianqiang Wang; Wanxiang Lu; Rui Liu; Qiaoyan Tian; Yiming Sun; Keming Luo (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Odorant Binding Characteristics of Three Recombinant Odorant Binding Proteins in Microplitis mediator (Hymenoptera: Braconidae) - Keming Li; Shanning Wang; Kang Zhang; Liyan Ren; Abid Ali; Yongjun Zhang; Jingjiang Zhou; Yuyuan Guo (Journal of Chemical Ecology, 2014)

Neurotrophic Tyrosine Kinase Receptor Type 2 (NTRK2) Gene Associated with Treatment Response to Mood Stabilizers in Patients with Bipolar I Disorder - Zuowei Wang; Jinbo Fan; Keming Gao; Zezhi Li; Zhenghui Yi; Lingxiao Wang; Jia Huang; Chengmei Yuan; Wu Hong; Shunying Yu; Yiru Fang (Journal of Molecular Neuroscience, 2013)

Identification and characterization of SHORTENED UPPERMOST INTERNODE 1, a gene negatively regulating uppermost internode elongation in rice - Li Zhu; Jiang Hu; Keming Zhu; Yunxia Fang; Zhenyu Gao; Yinghong He; Guangheng Zhang; Longbiao Guo; Dali Zeng; Guojun Dong; Meixian Yan; Jian Liu; et al. (Plant Molecular Biology, 2011)

Isolation and promoter analysis of a chalcone synthase gene PtrCHS4 from Populus trichocarpa - Yiming Sun; Qiaoyan Tian; Li Yuan; Yuanzhong Jiang; Yan Huang; Min Sun; Shaohu Tang; Keming Luo (Plant Cell Reports, 2011)

Effects of confined space and near vision stimulation on refractive status and vitreous chamber depth in adolescent rhesus monkeys - YunXia Leng; WeiZhong Lan; KeMing Yu; BingQian Liu; ZhiKuan Yang; Zheng Li; XingWu Zhong; ShaoChong Zhang; Jian Ge (Science China Life Sciences, 2010)

The chitinase gene (Bbchit1) from Beauveria bassiana enhances resistance to Cytospora chrysosperma in Populus tomentosa Carr. - Zhichun Jia; Yimin Sun; Li Yuan; Qiaoyan Tian; Keming Luo (Biotechnology Letters, 2010)

Overexpression of Citrus junos mitochondrial citrate synthase gene in Nicotiana benthamiana confers aluminum tolerance - Wei Deng; Keming Luo; Zhengguo Li; Yingwu Yang; Nan Hu; Yu Wu (Planta, 2009)

An improved procedure for Agrobacterium-mediated transformation of trifoliate orange (Poncirus trifoliata L. Raf.) via indirect organogenesis - Xiuping Zou; Demou Li; Xiaoying Luo; Keming Luo; Yan Pei (In Vitro Cellular & Developmental Biology - Plant, 2008)

The cauliflower mosaic virus (CaMV) 35S promoter sequence alters the level and patterns of activity of adjacent tissue- and organ-specific gene promoters - Xuelian Zheng; Wei Deng; Keming Luo; Hui Duan; Yongqin Chen; Richard McAvoy; Shuiqing Song; Yan Pei; Yi Li (Plant Cell Reports, 2007)

Leaf senescence is delayed in tobacco plants expressing the maize knotted1 gene under the control of a wound-inducible promoter - Keming Luo; Wei Deng; Yuehua Xiao; Xuelian Zheng; Yi Li; Yan Pei (Plant Cell Reports, 2006)

In vitro regeneration and Agrobacterium-mediated genetic transformation of Euonymus alatus - Yongqin Chen; Litang Lu; Wei Deng; Xingyu Yang; Richard McAvoy; Degang Zhao; Yan Pei; Keming Luo; Hui Duan; William Smith; Chandra Thammina; Xuelian Zheng; et al. (Plant Cell Reports, 2006)

The maize Knotted1 gene is an effective positive selectable marker gene for Agrobacterium-mediated tobacco transformation - Keming Luo; Xuelian Zheng; Yongqin Chen; Yuehua Xiao; Degang Zhao; Richard McAvoy; Yan Pei; Yi Li (Plant Cell Reports, 2006)